Fire and feminine presences in Eguren 's poetry - Lopez Maguiña, Santiago (2004)
The "feminine" in Eguren's poetry is expressed through figures of fire,warmth, heat, light and lacerating impressions associated with interna!movements of quick rhythm, expansive modulations and motions implyingdissolution and fragmentation, clearly identified with affection or eroticpassion. On the contrary, the "masculine", especial! y the first presence,that which senses the feminine, are figures of coldness and darknessrelated to narcotic affection.